2021
DOI: 10.1371/journal.pone.0247275
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a prediction model for tocilizumab failure in hospitalized patients with SARS-CoV-2 infection

Abstract: Background The aim of this secondary analysis of the TESEO cohort is to identify, early in the course of treatment with tocilizumab, factors associated with the risk of progressing to mechanical ventilation and death and develop a risk score to estimate the risk of this outcome according to patients’ profile. Methods Patients with COVID-19 severe pneumonia receiving standard of care + tocilizumab who were alive and free from mechanical ventilation at day 6 after treatment initiation were included in this ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 20 publications
0
9
0
3
Order By: Relevance
“…The Authors combined these variables in the CERRAHPASA-PREDICT score, whose positive and negative predictive values were 94.5% and 92.9%, respectively [29] . In another study enrolling two-hundreds and sixty-six COVID-19 patients treated with Tocilizumab, Mussini C et al identified sex, day-4, P/F after Tocilizumab administration, platelets count and CRP as independent risk factors for treatment failure and associated with 28-day mortality and mechanical ventilation [30] . In their study 28-day mortality was 10%, while 15% of patients underwent mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Authors combined these variables in the CERRAHPASA-PREDICT score, whose positive and negative predictive values were 94.5% and 92.9%, respectively [29] . In another study enrolling two-hundreds and sixty-six COVID-19 patients treated with Tocilizumab, Mussini C et al identified sex, day-4, P/F after Tocilizumab administration, platelets count and CRP as independent risk factors for treatment failure and associated with 28-day mortality and mechanical ventilation [30] . In their study 28-day mortality was 10%, while 15% of patients underwent mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…In their study 28-day mortality was 10%, while 15% of patients underwent mechanical ventilation. Combining these variables, the Authors proposed a predictive score with an area under the receiving operating curve of 0.80 [30] . In one hundred and twenty COVID-19 patients treated with Tocilizumab, Sarabia de Ardanaz L et al found that patients who died had significantly higher values of lactate dehydrogenase, CRP, troponin I, lower levels of platelets and lymphocytes and lower P/F [31] .…”
Section: Discussionmentioning
confidence: 99%
“…Mussini et al also tried to identify and model the predictors for tocilizumab failure. Their model reached a cross-validation-corrected AUC of 0.87 for a composite outcome measure of being on mechanical ventilation or mortality on the 28th day following the initiation of treatment, including gender, CRP, baseline platelet count, and PFR on the fourth day following tocilizumab administration [ 23 ]. However, the standard of care in their study cohort was hydroxychloroquine, lopinavir, and anticoagulation, which does not reflect current practice.…”
Section: Discussionmentioning
confidence: 99%
“…Careful patient selection and timing for IL-6 (receptor) antagonist treatment in COVID-19 patients is crucial 15 17 , especially considering the increased risk of side effects—neutropenia, impaired liver function and secondary infections—when IL-6 (receptor) antagonists were used. Our analyses suggested that Il-6 (receptor) antagonist treatment is beneficial in reducing mortality for patients with a high baseline risk of mortality, while it may be harmful for patients with a low baseline risk of mortality.…”
Section: Discussionmentioning
confidence: 99%